Enhancing Communicative Competence Through Kurikulum Merdeka: Insights For English Language Educators - Kadek Feni Aryati (AL-MIKRAJ Jurnal Studi Islam dan Humaniora, 2023)
This study aims to enhancing communicative competence through the independent curriculum: insights for english language educators. This research is a literature review. Data collection techniques are documentation from journal sources and relevant literature such as Google Scholar. Data analysis with critical literature. research results of The Merdeka curriculum, which focuses on developing communicative competence in learning English, has significant potential in advancing students' language skills. By strengthening aspects of communication, both oral and written, this approach seeks to improve students' ability to interact and communicate effectively in various contexts. English educators have a central role in implementing this approach by providing opportunities for students to practice and deepen their understanding of English through real experiences. Thus, the Independent Curriculum offers a promising outlook for educators in developing students' communicative competencies that are relevant and competitive in the current global era.